2021
DOI: 10.1002/elsa.202100146
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical studies of WO3‐based nanomaterials for environmental, energy and gas sensing applications

Abstract: The increase of pollutants in the environment and the rapid decrease of nonrenewable energy resources are putting immense pressure on ecosystems. Semiconductor oxides possess some unique properties that may provide a foundation for the development of advanced functional materials to address the pressing environmental and energy issues. Among various metal oxides, WO 3 based nanomaterials with an array of morphologies and sizes can be employed in a wide range of applications, including photocatalysis, water spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
(178 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure 3a, the exposed facet of WO 3 is significantly affected by the capping effect of Cl − ions, in which the exposed [002] facets will be promoted by increasing the amount of Cl − ions. Besides, metal doping was proposed to fabricate facet‐orientated WO 3 photoanode for PEC reactions [28] . Zheng et al.…”
Section: Design Of Wo3‐based Photocatalysts and Photoanodesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3a, the exposed facet of WO 3 is significantly affected by the capping effect of Cl − ions, in which the exposed [002] facets will be promoted by increasing the amount of Cl − ions. Besides, metal doping was proposed to fabricate facet‐orientated WO 3 photoanode for PEC reactions [28] . Zheng et al.…”
Section: Design Of Wo3‐based Photocatalysts and Photoanodesmentioning
confidence: 99%
“…Besides, metal doping was proposed to fabricate facet-orientated WO 3 photoanode for PEC reactions. [28] Zheng et al reported that introducing Bi 3 + ions into WO 3 film on FTO glass leads to a highly ordered [002]-oriented structure by spin coating a Bi-containing peroxotungstic acid as precursor followed by calcination. [26c] Kalanur et al incorporated Al atoms into WO 3 thin films with the [002] facets by hydrothermal method, in which the facet orientation was systematically tuned by controlling the at % of Al.…”
Section: Crystal Facet Optimizationmentioning
confidence: 99%
“…Among these TM oxides, tungsten trioxide (WO 3 ) has shown excellent potential to be used as an electrode material in SCs . The tunnel-like structure of WO 3 makes an easy ion insertion into the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Among these TM oxides, tungsten trioxide (WO 3 ) has shown excellent potential to be used as an electrode material in SCs. 14 The tunnel-like structure of WO 3 makes an easy ion insertion into the electrolyte. Its advantages include high thermal stability, corrosion resistance, multiple valency, wide negative potential range, and natural abundance.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Common deposition processes for these layers involve techniques such as chemical vapor deposition, e-beam evaporation, and sputtering, while electrodeposition, solvothermal, and sol–gel methods are popular choices among solution-based processes. 17–21 Solution processes offer significant advantages over the others due to allowing the use of low-cost equipment and enabling bulk production in a shorter time frame. Moreover, they facilitate the production of desired nanostructures with large surface areas, thereby promoting high electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%